Coronary Artery Bypass Grafting or Fractional Flow Reserve–Guided Percutaneous Coronary Intervention in Diabetic Patients With Multivessel Disease. (October 2020) - Di Gioia, Giuseppe; Soto Flores, Nina; Franco, Danilo; Colaiori, Iginio; Sonck, Jeroen; Gigante, Carlo; Kodeboina, Monika; Bartunek, Jozef; Vanderheyden, Marc; Van Praet, Frank; Casselman, Filip; Degriek, Ivan; et al.
Abstract : Background: In diabetic patients with multivessel coronary artery disease, coronary artery bypass grafting (CABG) has shown long-term benefits over percutaneous coronary intervention (PCI). Physiology-guided PCI has shown to improve clinical outcomes in multivessel coronary artery disease, though its impact in diabetic patients has never been investigated. We evaluated long-term clinical outcomes of diabetic patients with multivessel coronary artery disease treated with fractional flow reserve (FFR)–guided PCI compared with CABG. Methods: From 2010 to 2018, 4622 diabetic patients undergoing coronary angiography were screened for inclusion. The inclusion criterion was the presence of at least 2-vessel disease defined as with diameter stenosis ≥50%, in which at least 1 intermediate stenosis (diameter stenosis, 30%–70%) was treated or deferred according to FFR. Inverse probability of treatment weighting analysis was used to account for baseline differences with a contemporary cohort of patients treated with CABG. The primary end point was major adverse cardiovascular and cerebrovascular events, defined as all-cause death, myocardial infarction, revascularization, or stroke. Results: A total of 418 patients were included in the analysis. Among them, 209 patients underwent CABG and 209 FFR-guided PCI. At 5 years, the incidence of major adverse cardiovascular and cerebrovascular events was higher in the FFR-guided PCI versus the CABG group (44.5% versus 31.9%; hazard ratio, 1.60 [95% CI, 1.15–2.22]; P =0.005). No difference was found in the composite of all-cause death, myocardial infarction, or stroke (28.8% versus 27.5%; hazard ratio, 1.05 [95% CI, 0.72–1.53]; P =0.81). Repeat revascularization was more frequent with FFR-guided PCI (24.9% versus 8.2%; hazard ratio, 3.51 [95% CI, 1.93–6.40]; P <0.001). Conclusions: In diabetic patients with multivessel coronary artery disease, CABG was associated with a lower rate of major adverse cardiovascular and cerebrovascular events compared with FFR-guided PCI, driven by a higher rate of repeat revascularization. At 5-year follow-up, no difference was observed in the composite of all-cause death, myocardial infarction, or stroke between CABG and FFR-guided PCI. Abstract : Supplemental Digital Content is available in the text.